Serum Lactic Acid Following Aneurysmal Subarachnoid Hemorrhage Is a Marker of Disease Severity but Is Not Associated With Hospital Outcomes - Poblete, Roy A.; Cen, Steven Yong; Zheng, Ling; Emanuel, Benjamin A. (Frontiers in Neurology, 2018)
Background: Following aneurysmal subarachnoid hemorrhage, peripherally-drawn lactic acid has been associated with poor outcomes; however, its clinical significance is unknown. We investigated admission factors and patient outcomes associated with serum lactic acid in this population. Methods: This was a retrospective observational study of 105 consecutive patients with serum lactate collected within 24 h of admission. Primary objectives were to determine the incidence of admission lactic acidemia, and factors positively and negatively associated with lactate levels. We also sought to determine if admission lactic acidemia was associated with patient outcomes, including vasospasm, delayed cerebral ischemia, mortality, and discharge disposition. Results: Admission serum lactic acid was elevated in 56 patients (53% of the cohort). Levels were positively associated with Hunt & Hess and modified Fisher grade, glucose, troponin I and white blood cell counts, and negatively associated with GCS and ventilator-free days. Admission lactate was not associated with the development of vasospasm or delayed cerebral ischemia. Patients with elevated lactic acid more often died during hospitalization, and less often were discharged home. After adjusting for other predictors of poor outcome, the adjusted odds of inpatient mortality (OR 0.97, 95% CI 0.79–1.20; p = 0.80) and discharge to home (OR 1.00, 95% CI 0.80–1.26; p = 0.97) was not associated with admission lactic acid. Conclusions: Early serum lactic acid elevation is common following aneurysmal subarachnoid hemorrhage and is associated with the clinical and radiographic grade of hemorrhage. Levels did not independently predict short-term outcomes when adjusted for established predictors of poor outcome. Further study is needed to determine the clinical significance of peripherally-drawn lactic acid in aneurysmal subarachnoid hemorrhage.